1894. Sensitivity of Symptom-Based Screening for COVID-19 in Active Duty Service Members. (15th December 2022) - Matthews, Zachary; Cybulski, Daniel; Frankel, Dianne; Kieffer, John; Casey, Theresa; Osuna, Angela; Marcus, Joseph E
Abstract: Background: Symptomatic COVID-19 screening has been a cornerstone of case identification during the pandemic. Despite the myriad of COVID-19 symptoms, screens have focused on fever, cough, and dyspnea. It is unknown how well these symptoms identify cases in a healthy military population. This study aims to evaluate the utility of symptom-based screening in identifying COVID-19 through different COVID-19 waves. Methods: A convenience sample of 600 active-duty service members who arrived at JBSA in 2021 and 2022 was included in this study. We compared 200 symptomatic service members who tested positive for COVID-19 in each of FEB-APR 2021 (prior to the emergence of the Delta variant), JUN-AUG 2021 (Delta variant was predominant), and JAN 2022 (Omicron variant was predominant). Collected data included test date, reported symptoms, and vaccination status. Comparisons were conducted via Chi-Square or Fisher's Exact test. Results: Of the 600 symptomatic active-duty service members who tested positive for COVID-19, the most common symptoms were sore throat (n=385, 64%), headache (n=334, 56%), and cough (n=314, 52%). While sore throat was the most prominent symptom during Delta (n=140, 70%) and Omicron (n=153, 77%), headache was the most common prior to Delta (n=93, 47%). There were significant differences in symptoms by vaccination status (Table 2). Overall, screening for fever, cough, and dyspnea had a 65.1% sensitivity in this cohort (Table 3) with its lowest sensitivity in the pre-Delta cohort (53.5%) and highest sensitivity in the fully vaccinated Omicron cohort (78.3%). Conclusion: In this descriptive cross-sectional study evaluating symptomatic military members with COVID-19, symptom prevalence varied based on the predominant COVID-19 variant as well as patients' vaccination status. As screening strategies evolve with the pandemic, changing symptom prevalence should be considered. Disclosures: All Authors : No reported disclosures.